African Low‐Level Jets and Their Importance for Water Vapor Transport and Rainfall. Issue 1 (15th January 2021) - Munday, Callum; Washington, Richard; Hart, Neil
Abstract: Uncertainty in the future evolution of tropical rainfall is linked to circulation changes under warming. In Africa, a key barrier to interpreting rainfall changes is our limited understanding of water vapor transport across the continent. Here, we show that a series of nocturnal easterly Low‐Level Jets (LLJs), which form in the valleys punctuating the East African rift system, transport the majority of water vapor to central Africa from the Indian Ocean. There is a robust connection between strengthened LLJs and drought in eastern and southern Africa at interannual timescales, mediated by an increase in low‐level divergence and water vapor export. Analysis of climate model simulations at a wide range of resolutions (250–4.5 km) suggests that grid lengths <60 km are needed to simulate the salient structures of LLJs. The failure of coarse resolution models to capture LLJs is linked with biases in rainfall climatology and variability across the continent. Plain Language Summary: Africa is one of the continents least responsible for climate change but will bear a disproportionate share of its impact, particularly through changes to droughts and floods. An important task for climate scientists is therefore to understand possible future changes to African rainfall. Unfortunately, this task is made difficult by large gaps in our knowledge of the basic mechanics of the climate system over Africa. One of these gaps is in our understanding of how water vapor—which is a key ingredient for rainfall—travels from the Indian Ocean into the African interior. Here, we show that over 200, 000 tonnes of water vapor are transported each second through a series of invisible rivers, which flow through the atmosphere in valleys interrupting the high mountains of the East African Rift System. The models that we use to project rainfall change can capture the structure of these invisible rivers, but only if they represent the mountains of tropical Africa realistically. Key Points: Topographically constrained nocturnal low‐level jets dominate water vapor transport from the Indian Ocean to the African interior Drought is prevalent in the jet entrance regions across eastern and southern Africa during years with strong jets Coarse resolution climate models do not simulate key low‐level jets: A failure which contributes to errors in simulated rainfall